Konsep Ketenangan Jiwa Menurut Al-Qusyairi - Ema Nurlaila; Nabilla Kartika Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Koran is considered a universal guide for humans until the end of time, emphasizing that a person's glory is not determined by wealth or physical appearance, but rather by the level of piety. The Prophet's hadith also emphasizes that Allah SWT watches over a person's heart and actions, not just his physical condition. A pure soul will produce good deeds, bringing us to a discussion of the soul in the context of psychology. Psychology, as a science that studies human behavior and relationships between humans, finds relevance in the concept of the soul or